Pojecie „biedy" w jezyku polskim, francuskim, angielskim - Dyoniziak, Jolanta (Studia Romanica Posnaniensia, 2005)
The aim of this article is the semantic analysis of the lexeme bieda in Polish, French and English. The author shows that the semantic contents of this lexeme in Polish is different than in the other two languages. The author claims that owing to a large amount of usages of the lexeme typical only for our language, it is a specific, cultural language item.